Imaging parasites at different scales - Frischknecht, Friedrich (Cell host and microbe, 2010)
Pathogens interact with their hosts at different spatial and temporal scales. Studying these interactions therefore requires a wide range of imaging tools and approaches that bridge physics and biology, as shown by this Minireview focusing on recent studies of the causative agents of malaria, toxoplasmosis, and sleeping sickness.
Gesehen am 17.10.2023